Cancer nanotechnology - Jagdale, Swati C; Shah, Tejas P; Kuchekar, Bhanudas S; Chabukswar, Aniruddha R; Baviskar, Dhiraj T (Asian Journal of Pharmaceutics (AJP), 2014)
Cancer nanotechnology is the latest trend in cancer therapy. It helps the pharmacist to formulate the product with maximum therapeutic value and minimum or negligible range side effects. Cancer is the disease in which the abnormal cells are quite similar to the normal cell with just minute functional or genetic change. Thus, it is very hard to target the abnormal cells by the conventional method of the drug delivery system. Nanotechnology is probably the only method that can be used for site-specific action without causing the side effects by killing the normal cells. This review article describes the possible way to exploit the nanotechnology to targeted drug therapy in cancer. The various methods used are: systemic delivery systems, passive targeting, active targeting, intracellular delivery, subcellular localization, and nanoparticle drugs. Different cancer detection techniques like carbon nanotubes, nanorods, and biosensors are also available. This review article gives an idea about the possible potential of nanotechnology in drug delivery, drug targeting, and the diagnosis of cancer.